Review on the Use of Nanofillers in Polyurethane Coating Systems for Different Coating Applications - Deshmukh, Gauri P.; Mahanwar, Prakash A. (Journal of Coating Science and Technology, 2019)
Polyurethane (PU) is the most common, versatile and researched material in the world. It is widely used in many applications such as medical, automotive and industrial fields. It can be found in products such as furniture, coatings, adhesives, construction materials, Paints, elastomers, insulators, elastic fibres, foams, integral skins, etc. because it has extraordinary properties and the facility to tailor-made various formulations according to property requirement using different raw materials which are available. Though the material is having fascinating properties the material is also associated with various problems such as inferior coating properties. Inorganic pigments and fillers are dispersed in organic components and binders to improve different properties of the coating. This paper is intended to review the various nanofillers used in different PU coating systems. It gives a general introduction about the various fillers and it’s classification, Mechanism by which the filler enhances the mechanical properties of the materials, various factors which affect the properties of the coatings. Various methods of incorporation of fillers in the coating systems are discussed. Various nanofillers such as SiO2(Silicon Dioxide), TiO2(Titanium Dioxide), AL2O3(Aluminium Oxide), antimony doped tin oxide (ATO), BaSO4(Barium Sulphate), FE2O3(Ferric Oxide) as well as carbon nanotubes, graphene derived fillers and nano-diamonds are discussed in detail. The importance and effect of surface modification of fillers to enhance coating properties are also discussed along with challenges associated with polyurethane coatings and future trends.